A modified procedure of T-tube maneuver to treat tracheal total obstruction involving ablative bronchoscopy sparing open surgical interventionCentral MessagePerspective - Sen-Ei Shai, MD, PhD; Yi-Ling Lai, MS; Chi-Wei Hsieh, MD; Shih-Chieh Hung, MD, PhD (JTCVS Techniques)
Objectives: The study objectives were to test an innovative T-tube procedure involving ablative bronchoscopy for the treatment of total airway occlusion and to orchestrate a safe and nontraumatic maneuver to treat intricate subglottic stenosis amenable for substituting the conventional surgical intervention. Methods: This was an uncontrolled single-center cohort study on 1254 patients from January 2001 to June 2021. Patients underwent the modified T-tube procedure treatment for tracheal stenosis. Only 42 patients were included in the study because they had full records for subglottic total occlusion sitting tracheostomy. The ablative bronchoscopy, aided by a fixed suspending laryngoscope, was applied to retunnel their total airway occlusion. T-tube revision and removal were conducted under general anesthesia with laryngeal mask airway aid during follow-up. Results: The primary outcome was 90-day mortality. The secondary outcome was 90-day morbidity. The 42 patients included in the study had a mean age of 52.29 years (range, 9-84 years) with 22 men (52.38%). Their mean length of hospital stay was 13.67 days (range, 2-45 days). Their mean operation time was 73 minutes (range, 43-256 minutes). Their mean length of the tracheal stenosis was 2.8 cm (range, 0.8-6.3 cm). Outcomes were good in 29 patients (69.05%), satisfactory in 10 patients (23.81%), and considered failures in 3 patients (7.14%). A total of 16 patients (38.10%) underwent decannulation, and 3 patients (7.14%) were shifted to a Shiley tracheostomy. All 42 patients had a median follow-up of 6.2 years (range, 1.5-16.3 years). Conclusions: The modified T-tube procedure, which offered both resilience and versatility, improved the conventional technique in treating those patients experiencing total tracheal stenosis and who were unqualified for conventional open surgery.